1953
DOI: 10.1111/j.1744-7348.1953.tb01093.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF INFECTION WITH NOSEMA APIS ON THE ACTIVITIES AND LONGEVITY OF THE WORKER HONEYBEE

Abstract: Infection of the adult worker honeybee with Nosema apis reduces or obviates brood feeding and causes her to commence foraging earlier than a healthy bee. The length of foraging activity and the total length of life of infected bees is reduced.In colonies infected with N . apis the rate of brood rearing is severely depressed during April, May and June, the degree of depression being proportional to the percentage infection.Infection decreases during July, August and September, and consequently the rate of brood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Infection of workers by N. apis retards or inhibits development of the pharyngeal salivary (33), compromising the feeding of young larvae. A fairly high proportion of the eggs laid by the queen of a colony suffering from nosemosis fail to produce pupae, while artificially infected pupae are resistant to infection (14). The bee population begins to decrease as Nosema infection spreads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection of workers by N. apis retards or inhibits development of the pharyngeal salivary (33), compromising the feeding of young larvae. A fairly high proportion of the eggs laid by the queen of a colony suffering from nosemosis fail to produce pupae, while artificially infected pupae are resistant to infection (14). The bee population begins to decrease as Nosema infection spreads.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evidence of the influence of the parasite on colonies is related to changes in the activity and longevity of the worker honeybee and queen (10,14). Infection of workers by N. apis retards or inhibits development of the pharyngeal salivary (33), compromising the feeding of young larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Once a worker grows old and switches to tasks outside the nest, a resident pathogen that infects only the brood or younger workers will have fewer opportunities to find other susceptible hosts and its transmission within the colony will be slower. This is why the precocious foraging observed in honeybees infected by the protozoan, Nosema apis (Hassanein, 1953;L'Arrivee, 1963;Wang & Moeller, 1970) or the sacbrood virus (Bailey & Fernando, 1972) could be a host adaptation to reduce the rate of disease transmission within the colony. Such a role for the speed of age polyethism schedule in pathogen transmission has also been proposed by SchmidHempel & Schmid-Hempel (1993) to explain their demonstration that rapidly multiplying variants of the trypanosome Crithidia bombi show a higher within-colony transmission than slower ones in the bumblebee, Bombus terrestris.…”
Section: Temporal Polyethismmentioning
confidence: 96%
“…There is an especially large body of data about honeybee pathogens (Morse and Flottum, 1997). Honeybee workers infected with Nosema apis start foraging earlier (Hassanein, 1953;Wang and Moeller, 1970;Woyciechowski and Moroń, 2009) and are more likely to collect food even during unfavorable weather (Woyciechowski and Kozłowski, 1998). In one study the precocious foraging of workers inoculated with Nosema spores was not confirmed, but there was no certainty that the inoculation was effective (Mattila and Otis, 2006).…”
Section: Influence Of Diseases Poisoning Injury and Other Harmful Fmentioning
confidence: 99%